The Assiniboine. Anthropological papers of the AMNH - Lowie, Robert Harry, 1883-1957. (New York : Published by order of the Trustees [of the American Museum of Natural History], 1909)
270 p., 3 leaves of plates : ill. 24 cm. Includes bibliographical references (p. 260-262).